The relationship and agreement between systemic and local breakpoints in locomotor and non-locomotor muscles during single-leg cycling - Tilp, Markus; Mosser, Nina; Schappacher-Tilp, Gudrun; Kruse, Annika; Birnbaumer, Philipp; Tschakert, Gerhard (Frontiers in Physiology, 2025)
IntroductionThere is a well-established relationship between the respiratory compensation point (RCP) and local muscular breakpoints determined from near-infrared spectroscopy (NIRS) and electromyography (EMG). However, these breakpoints have not yet been compared both in locomotor and non-locomotor muscles simultaneously in single-leg cycling exercise. Therefore, the aim of the study was to investigate the relationship and agreement between systemic and local breakpoints in locomotor and non-locomotor muscles.MethodData from twelve physically-active participants (25.5 ± 3.9 years, 176.1 ± 11.6 cm, 71.2 ± 9.4 kg, 4 females) who completed a continuous single-leg step incremental cycling test (10 W min-1) with their right leg were included in the analysis. Ventilation and gas exchange were recorded to determine RCP. Surface EMG (sEMG) and NIRS signals were measured from both vasti lateralis muscles and breakpoints were determined from root mean Q square sEMG and deoxygenated hemo- and myoglobin signal m[HHb].ResultsThere was no significant difference in the power output at RCP (127.3 ± 21.8 W) and local muscular breakpoints both from the locomotor (m[HHb]: 119.7 ± 23.6 W, sEMG: 126.6 ± 26.0 W) and non-locomotor (m[HHb]: 117.5 ± 17.9 W, sEMG: 126.1 ± 28.4 W) muscles. Breakpoints also showed significant (p < 0.01) correlations (r = 0.67–0.90, ICC = 0.80–0.94) to each other with weaker correlations in the non-locomotor muscle (r = 0.66–0.86, ICC = 0.74–0.90). Despite the strong correlations, high individual variability and weak limits of agreement (up to −32.5–46.5 W) and substantial absolute differences (10.2–16.7 W) were observed which indicates that these breakpoints cannot be used interchangeably.DiscussionThese findings offer further insights into the mechanistic relationship between local and systemic physiological response to exercise with increasing workload. We conclude that, despite strong correlations, local muscular breakpoints do not have to coincide with systemic boundaries of physiological domains.